Meeting the challenges of the 21st century: the fundamental importance of trust for transformation - Martin McKee; May CI van Schalkwyk; Rachel Greenley (BMC, 2024)
Abstract Background This paper is one of a collection on challenges facing health systems in the future. One obvious challenge is how to transform to meet changing health needs and take advantage of emerging treatment opportunities. However, we argue that effective transformations are only possible if there is trust in the health system. Main body We focus on three of the many relationships that require trust in health systems, trust by patients and the public, by health workers, and by politicians. Unfortunately, we are seeing a concerning loss of trust in these relationships and, for too long, the importance of trust to health policymaking and health system functioning has been overlooked and under-valued. We contend that trust must be given the attention, time, and resources it warrants as an indispensable element of any health system and, in this paper, we review why trust is so important in health systems, how trust has been thought about by scholars from different disciplines, what we know about its place in health systems, and how we can give it greater prominence in research and policy. Conclusion Trust is essential if health systems are to meet the challenges of the 21st century but it is too often overlooked or, in some cases, undermined.